Doing Good in the Neighborhood? The Effect of Coethnic Concentration on the Educational Attainment of Mexican, Filipino, and Vietnamese Children of Immigrants - Rennie Lee (Revista Internacional de Sociología de la Educación, 2016)
An enduring puzzle in social sci ence literature is that immigrants‘ children belonging to Asian subgroups consistently outperform their Latino counterparts even after parents‘ socioeconomic background is considered. These disparities may be explained by differences in the coethnic commun ity. Using the Children of Immigrants Longitudinal Data in California, this study quantitatively examines whether living with more coethnics affects the educational attainment of Mexican, Vietnamese, and Filipino children of immigrants. The results indicat e that Vietnamese children benefit from living with a higher number of coethnics but Mexicans and Filipinos do not. The enduring Vietnamese effect may be attributed to underlying social characteristics of the Vietnamese community, such as their refugee sta tus or norms about success. Overall, the effect of coethnic neighbors on education depends on immigrants‘ aggregate characteristics.